Trees, shrubs and lawn: Acoustic effects in urban parks - Demaria, I.; Colorado, D. (Revista de la Universidad del Zulia, 2020)
Acoustic pollution is an important environmental issue for city quality indexes. Policy development attempts to assess and control noise levels through zoning, which is specified in the ‘noise map’. Citizens are entitled to reliable acoustic index regarding these levels in city parks. The available mapping systems are based on numerical models which do not take into account sound attenuation that green areas can generate. Urban parks are composed of multiple elements and coverage including trees, shrubs, grasslands, soils and pavements, all having a different effect on sound waves. By means of the following paper, The main factors that influence acoustic quality in urban parks will be investigated. In addition, a model to assess the influence of vegetation surfaces will be also proposed.